FAKTOR KEUANGAN DAN CORPORATE GOVERNANCE TERHADAP INTERNET FINANCIAL AND SUSTAINIBILITY REPORTING (Studi Empiris pada Perusahaan Manufaktur yang Listed di Bursa Efek Indonesia Tahun 2016) - Immanuela, Intan; Purbandari, Theresia (Widya Warta, 2021)
The company has the responsibility towards stakeholders to convey information, both financial reports and other important information. Disclosure of financial and non-financial information is known as Internet Financial and Sustainability Reporting (IFSR). This study examined the effect of financial factors and corporate governance on Internet Financial and Sustainability Reporting (IFSR). The sample used was a manufacturing company listed on the Indonesia Stock Exchange in 2016. The sampling technique was purposive sampling. Hypothesis testing used multiple linear regression analysis. The results showed that the variables of company size, profitability, institutional ownership, governance committee, and audit committee had no effect on Internet Financial and Sustainability Reporting (IFSR). In contrast, the board of commissioner variable had a positive effect on Internet Financial and Sustainability Reporting (IFSR).